Processing Technologies for Bee Products: An Overview of Recent Developments and Perspectives - Luo, Xuan; Dong, Yating; Gu, Chen; Zhang, Xueli; Ma, Haile (Frontiers in Nutrition, 2021)
Increased demand for a more balanced, healthy, and safe diet has accelerated studies on natural bee products (including honey, bee bread, bee collected pollen royal jelly, propolis, beeswax, and bee venom) over the past decade. Advanced food processing techniques, such as ultrasonication and microwave and infrared (IR) irradiation, either has gained popularity as alternatives or combined with conventional processing techniques for diverse applications in apiculture products at laboratory or industrial scale. The processing techniques used for each bee products have comprehensively summarized in this review, including drying (traditional drying, infrared drying, microwave-assisted traditional drying or vacuum drying, and low temperature high velocity-assisted fluidized bed drying), storage, extraction, isolation, and identification; the assessment methods related to the quality control of bee products are also fully mentioned. The different processing techniques applied in bee products aim to provide more healthy active ingredients largely and effectively. Furthermore, improved the product quality with a shorter processing time and reduced operational cost are achieved using conventional or emerging processing techniques. This review will increase the positive ratings of the combined new processing techniques according to the needs of the bee products. The importance of the models for process optimization on a large scale is also emphasized in the future.